Innovative approaches to the organization of distance education of students of the teaching university - Shtonda, Oksana; Sira, Iryna; Proskurnia, Oleksii (Scientific notes of the pedagogical department, 2023)
Problem formulation. This article presents the results of the analysis of the role of active and interactive methods of pedagogical interaction in the process of distance learning of students of a pedagogical university. The relevance of the study is due to the need to design the content of educational programs of professional training using distance educational technologies in the context of the activity paradigm of education, targeted improvement of its efficiency and quality.The purpose of the article is the analysis of innovative approaches to the organization of distance learning of students of pedagogical universities, namely the identification of active and interactive methods of pedagogical interaction in the process of distance learning.